(untitled) (Medical Forum Monthly, 2024)
Objectives: To assess knowledge of physicians of tertiary care hospitals of Peshawar about schizophrenia. Study Design: Cross Sectional Place and Duration of Study: This study was carried out at Lady Reading Hospital, Khyber Teaching Hospital and Hayatabad Medical Complex, Peshawar from 10/09/2009 to 10/10/2010. Materials and Methods: It was cross sectional study conducted at tertiary care hospitals of Peshawar from 10th September to 2009 to 10th September 2010. 100 Physicians were asked to answer a Performa consisting of two portions namely, General Information and knowledge about Schizophrenia. Results: Ninety Six percent of the physicians who participated in the study were males while four percent were female. Out of 100 physicians, 2% treated more than 10 patients annually, 3% treated 6-9 patients, 12% treated 3-5 patients and 13% treated 1-2 patients annually while 70% physicians didn’t treat any diagnosed case of schizophrenia in a year. 6% of the physician diagnosed more than 5 new cases, 18% diagnosed 3-5 new cases and 42% diagnoses 1-2 new cases annually while 34% didn’t diagnose any new case in year’s time. 44% of physician had good knowledge about schizophrenia while 56% had poor knowledge. Conclusion: Most of the physicians have poor knowledge about schizophrenia.